Chemical features of the oligochitosan-glycated caseinate digest and its enhanced protection on barrier function of the acrylamide-injured IEC-6 cells. (30th August 2019) - Shi, Jia; Zhao, Xin-Huai
Highlights: Tryptic digest of the oligochitosan-glycated caseinate had enhanced bioactivity. This digest alleviated the acrylamide-induced barrier dysfunction in IEC-6 cells. TJ-related 6 genes and 3 proteins were all up-regulated in the treated cells. The caseinate glycation thus contributed to improved intestinal barrier function. Abstract: Whether caseinate oligochitosan-glycation of the transglutaminase-type followed by trypsin digestion could lead to better protection against the acrylamide-induced cell barrier damage was investigated. Compared with caseinate digest, glycated caseinate digest had similar amount of Lys and Arg but lower –NH2 (0.557 versus 0.508 mol/kg protein) and total amide (1.12 versus 1.05 mol/kg protein) contents, and contained glucosamine at 5.74 g/kg protein. Acrylamide damaged barrier function of IEC-6 cells efficiently, leading to increased paracellular permeability and lactate dehydrogenase release, decreased trans-epithelial electrical resistance, and destroyed tight junction. The two digests alleviated these barrier dysfunctions via reversing index values. Three cellular proteins (ZO-1, occludin, and claudin-1) crucial to tight junction were up-regulated by the two digests. Furthermore, glycated caseinate digest was always more effective than caseinate digest to improve cell barrier function. This oligochitosan glycation is thus desired, as it ensures glycated protein digest with higher potential to protect intestinal barrier function.